Emprego da citometria de fluxo na avaliação do perfil imunofenotípico de pacientes com leucemia linfocítica crônica - Lopes, Maria Cleide de Araujo (2010)
Chronic lymphocytic leukemia (B-CLL) is a clonal proliferation of mature B lymphocytes characterized by indolent clinical course. Biologically this clonallity is characterized by low expression of surface immunoglobulin (sIg) with restriction to a single immunoglobulin light chain associated with high expression of CD5 antigen and positivity to B cell antigens lymphocytes such as CD19, CD20 and CD23 and negativity to FMC7. The immunological profile and morphological analysis of lymphoid cells are the main means for the differential diagnosis of B-CLL from other chronic lymphoproliferative diseases. The aim of this study was to evaluate the expression pattern of a variety of membrane antigens in leukemic cells originating from patients with B-CLL. In this study, peripheral blood samples from 80 patients with B-CLL were analyzed by multiparametric flow cytometry in addition to routine hematologic exams, using a panel of monoclonal antibodies (MoAb): CD45/CD14, CD3/CD19/CD45, CD4/CD8 / CD3, CD20/CD5/CD3, CD3/CD16-56/CD45, CD2/CD7, FMC7/CD23, CD103/CD22/CD20, HLADR/CD38, CD10/CD19, CD1a, CD11b and also IgM/gD, kappa and lambda immunoglobulin light chains for the detection of surface immunoglobulin and clonal restriction for immunoglobulin light chain. The Hematological data were obtained from the hematological analyzer and cytomorphological analysis in blood film stained by Leishmann. The study samples consisted of 45 men and 35 women, ages ranging from 55 to 84 years (mean 65 years). Complete white blood count showed count ranging from 10.0 to 42.0 x 109/l. (mean 50.0 x 109/l) and lymphocytes count greater than 5.0 x 109/l in all cases. The neoplastic cells displayed B-CLL phenotype (CD5+/CD19+/CD20+/HLADR+/CD23+) in the vast majority of the cases, associated to failed to stain for T cell markers (CD1a, CD2, CD4, CD3, CD7, CD8), CD103, CD14 and FMC7. Leukemic cells of most patients also expressed low intensity of IgM and IgD with restricted kappa light chain, in most cases (59,7%). This observation highlights the importance of immunophenotyping for correct diagnosis of chronic lymphoproliferative syndromes and the panel of MoAb used was sufficient for diagnostic confirmation of B-CLL